Wild and lesser-known fruit germplasm in JNTBGRI: An approach for ex-situ conservation - Nazarudeen, A; Shareef, S M; Kalesh, K S; Salim, M; Hussain, A; Shaju, T; Rajvikraman, R; Prakashkumar, R (Indian Horticulture, 2022)
The conservation activities of wild fruits are in fact a safety measure to protect the lesser-known and under-exploited native fruit germplasm from all kinds of depletion. JNTBGRI is the pioneer institute in Kerala to come up with such a prolific scheme to protect thevast reservoir of wild fruits germplasm bounded in its wilderness. A total of 648 live accessions belonging to 184 species are maintained in the Institute’s conservatory. Within the next few years, more wild fruit plants will be brought out for conservation and popularization as an alternative unconventional resource, adding substantially to the fruit basket of the State. In the coming years,novel strategies will be established for bringing such unconventional fruit germplasm into the limelight of active research so as to catch up the attention of plant breeders, agriculturists, industrialists, etc.